Food safety risk profiling of arsenic in regularly milled local rice (Oryza sativa L.) in the Philippines - Bayangos, Roel Anthony S.; Rustia, Abigail S. (Quezon City University of the Phiippines Diliman, 2025)
Arsenic is a naturally occurring element, and its inorganic form is highlighted to be more associated with lung, bladder, skin, kidney, liver, and prostate cancer. It is used in wood processes and preservation, and in agriculture (pesticides, herbicides, and insecticides). Recent studies showed that rice grain samples contained traces of inorganic arsenic due to it being typically planted in flooded waters. Given the importance of milled rice in the Filipino diet and the potential health risks from contamination with arsenic, this study conducted a formal food safety risk profiling of arsenic in regularly milled local rice by [1] determination of data gaps in the risk profiling of arsenic in regularly milled local rice by the Filipino consuming population; [2] identification and characterization of arsenic as a food hazard; [3] estimation of dietary exposure (DE) and risks based on uncertainties, variabilities, and assumptions; and [4] determination of available risk management options for arsenic in regularly milled local rice. The mean and high (97.5%) DEs, in mg/kg bw/d, of infants and preschool children (mean male=0.0026; mean female=0.0027; high male=0.0027; high female=0.0029), school-age children (mean male=0.0023; mean female=0.0023; high male=0.0024; high female=0.0024), adolescents (mean male=0.0019; mean female=0.0020; high male=0.0019; max female=0.0021), adults (mean male=0.0015; mean female=0.0017; high male=0.0016; high female=0.0017), and elderly (mean male=0.0012; mean female=0.0014; high male=0.0013; high female=0.0014) were calculated based on the equation provided by WHO (2020). The said DEs values are lower than the PTWI of inorganic arsenic to be 0.015 mg/kg set during the 33rd meeting in 1988 of the Joint Expert Committee for Food Additives (JECFA) (TRS 776-JECFA 33/27). The results suggested a low risk associated with arsenic in the consumption of regularly milled local rice among the Filipino population. However, JECFA withdrew the PTWI at its 72nd meeting in 2011 (TRS 959-JECFA 72). Nonetheless, the PTWI value was still used in this study to serve as a point of reference for the assessment of the calculated dietary exposure values.
In partial fulfillment for the Degree of Bachelor of Science in Food Technology
Thesis
Keywords: Food contamination; Food -- Safety measures; Food Safety; Arsenic -- Toxicology; Rice -- Philippines; Milled rice; Arsenic; Dietary exposure